Attitudes to mental illness: the effects of labels and symptoms - Found, Andrew; Duarte, Carlos (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2011)
OBJECTIVES: To investigate the effects of different Chinese terms for mental illness and related symptoms on the attitudes of adolescents towards sufferers of a mental illness. METHODS: A survey of 578 secondary school students attending 4 schools in Macao was conducted. Each student read a short passage about a new student with a mental illness joining their class. Different versions used different labels to refer to the illness of the new student. The symptoms describing the new student also varied: either describing positive symptoms of schizophrenia or mild negative symptoms only. The attitudes of participants to the new student described were measured. RESULTS: There were significantly more negative attitudes towards the sufferer of a mental illness referred to with a psychiatric label, compared with a general label 'illness'. Participants also expressed significantly more negative attitudes when positive symptoms of schizophrenia were used to describe the new student. The results are discussed in terms of the influence of labels and symptoms on attitudes towards mental illness. CONCLUSIONS: These results supported the existence of 2 additive costs in terms of negative attitudes towards sufferers of mental illness, one associated with the label and the other associated with the symptoms.
Keywords: Adolescent; Adolescent Behavior; Asian People; Attitude to Health; Female; Humans; Male; Mental Disorders; Stereotyping; Students; Surveys and Questionnaires; Young Adult